2010
DOI: 10.1007/s00392-010-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Serial changes of minimal stent malapposition not detected by intravascular ultrasound: follow-up optical coherence tomography study

Abstract: Morphologic changes of small-sized post-stent malapposition have not been sufficiently evaluated. We investigated serial changes of minimal post-stent malapposition with a follow-up optical coherence tomography (OCT) study. Post-stent OCT and intravascular ultrasound (IVUS) and follow-up OCT were performed in 26 patients with minimal post-stent malapposition. Serial changes of number and percent of malapposition struts, and mean extra-stent malapposition area were measured in OCT analysis. Zotarolimus-eluting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…A previous study comparing poststent OCT with IVUS showed that minimal acute stent malapposition was detected by OCT in 62% of patients but was not detected by IVUS. 16 Lesion characteristics, such as calcification and severe diameter stenosis, were identified as predictors of acute stent malapposition. Heavily calcified lesions are known to preclude stent apposition, despite highpressure balloon dilation or rotational atherectomy.…”
Section: Acute Stent Malappositionmentioning
confidence: 99%
“…A previous study comparing poststent OCT with IVUS showed that minimal acute stent malapposition was detected by OCT in 62% of patients but was not detected by IVUS. 16 Lesion characteristics, such as calcification and severe diameter stenosis, were identified as predictors of acute stent malapposition. Heavily calcified lesions are known to preclude stent apposition, despite highpressure balloon dilation or rotational atherectomy.…”
Section: Acute Stent Malappositionmentioning
confidence: 99%
“…The neointimal healing process after stenting might spontaneously correct ISA to some extent, integrating the malapposed regions into the vessel wall, as suggested by sequential quantitative studies with optical coherence tomography (OCT), which reported ISA volumes and percentage of ISA struts decreasing over time. [1][2][3][4] Other qualitative OCT studies have also speculated about some morphological patterns at follow-up and the hypothesis that they could represent the vascular response to acutely malapposed struts. 5 The reasons why the vascular biology succeeds in covering and even integrating some ISA regions into the vessel wall but not others remain poorly understood.…”
mentioning
confidence: 99%
“…Nevertheless, regions of minimal acute ISA size appear frequently covered and even totally integrated in the vessel wall at follow-up. 2,3 Thus, the question of what degree of acute ISA is worth correcting remains unanswered for the interventional cardiologist.…”
mentioning
confidence: 99%
“…The percent of malapposed struts signifi cantly decreased from 12.2 ± 11.0 % post-stent to 1.0 ± 2.2 % at the 6-month followup (P < 0.001). In those lesions with minimal malapposition, there was a signifi cant decrease in the mean extra-stent malapposition area from 0.35 ± 0.16 mm 2 post-stent to 0.04 ± 0.11 mm 2 at follow-up (P < 0.001) [ 38 ]. On the other hand, there are persistent malappositions and newly developed late stent malappositions detected at followup.…”
Section: Malappositionmentioning
confidence: 88%